Carcinoma of the colon in children - Büyükpamukçu, Münevver; Berberoğlu, Semha; Büyükpamukçu, Nebil; Sarıalioğlu, Faik; Kale, Gülsev; Akyüz, Canan; Kutluk, Tezer (The Turkish Journal of Pediatrics, 1996)
The symptoms, histology, extent and course of disease in 16 adolescents with colorectal carcinoma who were admitted to Hacettepe University Children’s Hospital between 1972 and 1990 are presented. Most patients presented with vague abdominal complaints. Twelve of the 16 patients had mucin-producing adenocarcinoma. Extensive disease at diagnosis and unresponsiveness to medical management were determined. Only one patient survived free of disease four years after diagnosis. Nine of the patients died between one day and one year following the initial surgery. The remaining six patients were very ill when they were discharged from the hospital, after which time no information was received concerning them.